2006
DOI: 10.1007/s11027-006-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Constructing a Social Vulnerability Index: An Application to Hurricane Storm Surges in a Developed Country

Abstract: vulnerability assessment, vulnerability indicators, vulnerability index, indicator weighting, Pareto ranking, social vulnerability, extreme weather events,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
220
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(231 citation statements)
references
References 17 publications
0
220
0
11
Order By: Relevance
“…Since three decades several works have been made to establish strategies and procedures for evaluating coastal vulnerability to climate change and other related aspects, accompanied with economics (Cutter et al 2003;Lewsey et al 2004;Vincent 2004;Rygel et al 2006;Phillips and Jones 2006;Hinkel et al 2009;Torresan et al 2012;Addo 2013;Tang et al 2013;Wolters and Kuenzer 2015;Denner et al 2015;Wu et al 2016). A summary of several methodologies established and applied globally is provided here.…”
Section: Coastal Vulnerability Appraisal Methodsmentioning
confidence: 99%
“…Since three decades several works have been made to establish strategies and procedures for evaluating coastal vulnerability to climate change and other related aspects, accompanied with economics (Cutter et al 2003;Lewsey et al 2004;Vincent 2004;Rygel et al 2006;Phillips and Jones 2006;Hinkel et al 2009;Torresan et al 2012;Addo 2013;Tang et al 2013;Wolters and Kuenzer 2015;Denner et al 2015;Wu et al 2016). A summary of several methodologies established and applied globally is provided here.…”
Section: Coastal Vulnerability Appraisal Methodsmentioning
confidence: 99%
“…Commonly used weighting procedures are mainly based on either statistical methods (Aleksandrova et al 2015) or participatory methods . Based on statistical methods of Pareto ranking, Rygel et al (2006) and Karmakar et al (2010), for example, demonstrated a method of aggregating vulnerability indicators that avoids the problems associated with assigning weights. The statistical based methods does not incorporate stakeholders' attitude in aggregation.…”
Section: Assessment Of Vulnerabilitymentioning
confidence: 99%
“…1 Issues such as race and ethnicity, socioeconomic class, gender and housing condition and tenure are recognised as among the most important characteristics for defining socially excluded populations (Cutter et al 2003, Tapsell et al 2002, Morrow 1999, Rygel et al 2006, Satterthwaite et al 2009.…”
Section: Place Social Exclusion and Climate Changementioning
confidence: 99%
“…Similarly single parent households are more at risk not only because they are frequently low income households (Rygel et al 2006), but also because of the added responsibilities in caring for dependent children (Clark et al 1998). Significant health problems such as long term illness or disability have also been found to be associated with elevated risk in the event of extreme weather impact (Morrow 1999).…”
Section: Place Social Exclusion and Climate Changementioning
confidence: 99%